Lords of the Mountains : Pre-Islamic Heritage along the Upper Indus in Pakistan - Hauptmann, Harald; OLIVIERI, Luca Maria (2024)
With his authoritative monograph, Lords of the Mountains. Pre-Islamic Heritage along the Upper Indus in Pakistan, Harald Hauptmann brought decades of research in the Karakoram region of northern Pakistan to an impressive conclusion. In a sense, this book (completed before his sudden death in 2018) is the scientific legacy of the last phase of his career. The book was edited by Luca M. Olivieri of Ca' Foscari University of Venice, head of the ISMEO and Ca' Foscari's Italian Archaeological Mission in Pakistan.